Excellent performance in vertical graphene-C60-graphene heterojunction phototransistors with a tunable bi-directionality. (June 2020) - Pan, Rui; Han, Jiayue; Zhang, Xingchao; Han, Qi; zhou, Hongxi; Liu, Xianchao; Gou, Jun; Jiang, Yadong; Wang, Jun
Abstract: Array integrated all-carbon phototransistor with high photoconductive gain and fast response speed is very attractive for researchers to realize broadband and tunable photo-imaging. Generally, the photoresponse is limited by the low light absorption of carbon materials while the detector array is limited by processing technology. Here, we patterned vertical graphene-C60 -graphene heterojunction using photolithograph and deep reactive ion etching method to achieve a sensitive (3.4 × 10 5 A/W), fast (23 ms) and broadband (405 nm–1550 nm) response. More interestingly, a bi-directional response photocurrent (positive and negative) has been observed, and the response intensity, speed and direction could adjust by changing gate voltage. The different charges transfer mechanism of positive and negative response of fabricated vertical heterojunction device was explored. What' more, we fabricated 250 × 250 vertical graphene/C60 film/graphene phototransistors array, which made it possible to realize a large-scale array detection in wide band with all-carbon material. Graphical abstract: Image 1